Stentoplasty (Cemented kyphoplasty with Stent) Under Biplane Digital Subtraction Angiography (Biplane DSA) - Buranakarl, Tayard; Jaisanuk, Kanoknard; Varatorn, Rergchai; Suchato, Chirotchana; Srisuphap, Sarij (The Bangkok Medical Journal, 2019)
Vertebral body augmentation with cement such as vertebroplasty and kyphoplasty are well established minimally invasive treatment options for osteoporotic and pathological vertebral compression fracture with highly successful results. The original technique of injection of polymethylmethacrylate (PMMA) bone cement into the compressed vertebral body directly is called “Vertebroplasty”. This technique proved to be a useful approach that could significantly reduce back pain immediately and help the aging patient return to normal activity in a few days with less morbidity than open internal fixation. However, injecting the bone cement directly into the vertebral compression fragment “vertebroplasty” cannot well restore the height of that compressed vertebra, which can cause segmental kyphosis. Biomechanical and clinical data show that the segmental kyphosis resulting from compression fractures, leads to an increased fracture risk of the adjacent vertebral levels,1, 2 that can cause recurrent pain, deformity and disability in the future. Vertebroplasty has no intrinsic mechanical method to restore vertebral height but relies on the elasticity of the fracture itself and patient positioning to induce lordosis. Also, the directed injection of bone cement into non-homogenous space of vertebral fragments can cause a high rate of extra-vertebral leakage that can lead to tremendous complications such as cord compression, embolism, neuropathic pain, paralysis or even death.